Responses of Endothelin-1 and Arterial Blood Pressure of Postmenopausal Women to Aerobic Exercise Training - Ahmad Qassemian; Farhad Daryanoush; Ebrahim Ghasemian; Elham Shakoor (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Endothelin-1 is a strong constrictor of blood vessels that is secreted by endothelial cells and identified as the strongest vascular constrictor. The aim of the present study was to investigate the effect of eight week aerobic exercise on the endothelin-1 concentration of plasma and its relationship with blood pressure in elderly postmenopausal women. Methods & Materials: A total of 20 menopausal women (with the average age of 67.85±5.67 years , height 153.50±7.7 cm, weight 66.16±11.96 kg, BMI of 28.15±4.98, fat percentage of 18.41±3.65, and WHR of 0.92±0.04) were selected and randomly assigned into two groups of ten each. The experimental group underwent eight weeks of aerobic training spanning across three sessions in a week with the intensity of 60 to 70% of maximum heart rate. The resting level of endothelin-1 concentration along with the systolic and diastolic blood pressure for each participant were measured and recorded before and after eight weeks of exercise .Paired t-test was used for investigating the changes within the group while the independent t-test was used for investigating the differences between the groups. Pearson correlation coefficient was used for investigating the relationship between endothelin-1 and blood pressure. A significance level less than 0.05 were considered to be significant. Results: The result of this study showed that one duration of aerobic exercise had a significant effect on endothelin-1 plasma density (P<0.01) and decreasing systolic (P<0.01) as well as diastolic(P=0.002) blood pressure in older women. A direct correlation was established between endothelin-1 and systolic blood pressure (P=0.59). Nevertheless, no correlation was noted between endothelin-1 and diastolic blood pressure (r=0.39). Conclusion: It was concluded that single duration of aerobic exercise with the agreed intensity and volume could decrease the systolic and diastolic blood pressure and the endothelin-1 concentration of plasma.